UJI GESER PELAT KOMPOSIT SERAT CARBON EPOXY SERTA PERBANDINGANNYA DENGAN ANALISIS FINITE ELEMENT METHOD (FEM) - Rachmayanti, Farida
Carbon composite structure is one of the materials commonly used on aircraft. To find out the quality of composite materials shear testing is necessary. Where material is pressed with the same magnitude until a process of deformation or displacement occurs (the process of shifting objects or changes in the position of the starting point and end point of an object). Composite testing of V-Notched Beam Method uses the basic procedure of ASTM D5379. The V-Notched test is carried out using an Instron machine with a capacity of 10 tons. Tests carried out in rooms with a temperature of 23 ° C and humidity of 55%. The testing speed on this machine is 2 mm / minute. From the test, the value of Basic Material Value (BMV) is obtained, namely: ? (strain), G12 (shear modulus) and S (shear strength). In addition, progressive failure stages (Maximum Stress, Tsai-Hill, Hoffman) from V-Notched specimens are also displayed. MSC. Patran Nastran provides facilities to conduct progressive failure analysis, with these facilities we can find out when first ply failure occurs, how the damage propagates and how much the ultimate failure load is. The test specimen material used is made of carbon epoxy type Cyctec Engineered Materials (Cycom 5276-1) with sizes according to ASTM D5379 standards. For UD material consists of 22 layers with a thickness of 3.4 mm while Fabric consists of 10 layers with a thickness of 2 mm. There are 4 types of test specimen configurations: UD 0 °, UD 90 °, Fabric 0 ° and Fabric 90 °. The test results of the four configuration specimens that will fail the fastest or damage are UD 90 °. The difference in average shear modulus compared to Cyctec ranges from 66.12% - 75.78%. Shear Strength UD ranges from 31.82% - 65.59% and shear strength Fabric: 5.81%. The smallest ultimate strength value UD 90 °: 47.897 N / mm2. Tsai Hill error failure criteria: 3.14%, Hoffman: 5.59% and Maximum Stress: 27.12%.